Migration and quality of landlocked Atlantic salmon smolt : Implications for conservation and management - Norrgård, Johnny R (Karlstads universitet, Institutionen för miljö- och livsvetenskaper, 2014)
Atlantic salmon Salmo salar has a complex life cycle, including long migrations and habitat shifts for both juveniles and adults. As such, salmon populations are vulnerable to habitat degradation and fragmentation along their migratory routes. This makes management and conservation a complex task requiring knowledge of salmon ecology at different temporal and spatial scales. In this thesis I highlight the use of a holistic life-history based approach in the conservation and management of wild and hatchery-reared salmon in regulated rivers and lakes. Small populations of wild-reproducing landlocked salmon and trout Salmo trutta exist in the regulated River Klarälven, Sweden. Since the 1930s, transportation of adult spawners upstream of eight dams has given the fish access to spawning grounds. The number of returning wild spawners became critically low in the 1960s, but stocking of hatchery smolts resulted in an increase in spawners that continues today. My data show that wild smolt may suffer high mortality due to multiple dam passages. To ensure viable populations of wild populations, future management should include both up- and downstream solutions that ensure connectivity in the system. The recreational and commercial salmonid fishery are maintained by compensatory stockings, yielding annual catches of about 75 tons, and a river return rate of hatchery fish of about 1%. As a large portion of the stocked smolts does not survive downstream migration to the lake, there has been discussion about the quality of the stocked smolt and about stocking strategies. Based on my studies, producing hatchery smolts more closely resembling wild-born conspecifics should result in reduced loss rates. I suggest changes in the hatchery and stocking procedures to increase the survival of stocked smolts. The results of my research should be applicable to other regulated systems, particularly those with mixed stocks of wild and hatchery salmonid populations. Atlantic salmon Salmo salar has a complex life cycle, including long ...